Stringency of Land-Use Regulation: Building Heights in US Cities - Jan K. Brueckner; Ruchi Singh (Center for Economic Studies and ifo Institute (CESifo), 2018)
This paper has explored the stringency of land-use regulation in US cities, focusing on building heights. Substantial stringency is present when regulated heights are far below free-market heights, while stringency is lower when the two values are closer. Using FAR as a height index, theory shows that the elasticity of the land price with respect to FAR is a proper stringency measure. This elasticity is estimated for five US cities by combining CoStar land-sales data with FAR values from local zoning maps, and the results show that New York and Washington, D.C., have stringent height regulations, while Chicago's and San Francisco's regulations are less stringent (Boston represents an intermediate case).
Keywords: R31; 330; building heights; FAR; stringency; regulation